China's health aid to African countries - (:unkn) unknown (My University, 2020)
China is increasingly present in Africa, where it is emerging as an important partner of States in the health sector. This study examines a range of factors that contribute to a better understanding of China's aid motivations to African countries in this field. The results show that they are complex and that they relate both to the needs of African countries and to China's specific interests.
Keywords: African Research